2018
DOI: 10.1111/1365-2745.13055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term variation in pollinator abundance and diversity on reproduction of a generalist plant

Abstract: Quantifying the benefits of pollinator abundance and diversity for plant reproduction is a critical challenge, especially given recent pollinator declines. Many studies test for pollen limitation (PL), but huge gaps remain in our understanding of how often and why plants experience PL. Most studies are limited to a few sites or years. Little existing research mechanistically links pollinator visitation with plant reproduction. Also, buffering against variability in visitation is a key but largely untested pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 54 publications
(113 reference statements)
1
15
0
Order By: Relevance
“…Floral neighbourhood conditions associated with high pollinator visitation did not always predict successful pollination, which aligns with the literature (de Waal et al, 2015;Hegland & Totland, 2012;Rodríguez-Pérez & Traveset, 2016;Thomson, 2019;Wagenius & Lyon, 2010), and reinforces the need to study the pollination as a process. As in other studies (Ison et al, 2018;Ison & Wagenius, 2014), Echinacea reproductive success declined as the flowering season progressed.…”
Section: Rates Of Pollination Successsupporting
confidence: 87%
“…Floral neighbourhood conditions associated with high pollinator visitation did not always predict successful pollination, which aligns with the literature (de Waal et al, 2015;Hegland & Totland, 2012;Rodríguez-Pérez & Traveset, 2016;Thomson, 2019;Wagenius & Lyon, 2010), and reinforces the need to study the pollination as a process. As in other studies (Ison et al, 2018;Ison & Wagenius, 2014), Echinacea reproductive success declined as the flowering season progressed.…”
Section: Rates Of Pollination Successsupporting
confidence: 87%
“…Pollination services are estimated to be worth annually $3 billion in the US alone (Losey & Vaughan, 2012) and upwards of $130 billion globally; but this is likely to be an underestimate, as putting a monetary value on ecosystem services is complex and overlooks the additional impact on people's well-being (Hanley et al, 2015). A recent study found that in certain environments the social wasp Vespula pennsylvanica was a more effective pollinator than the honey bee (Thomson, 2018). A recent study found that in certain environments the social wasp Vespula pennsylvanica was a more effective pollinator than the honey bee (Thomson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pollination services are not limited to bees: hoverflies, beetles, butterflies, wasps and bugs all contribute to pollination, but their contributions are not well recognised (Rader et al, 2016). A recent study found that in certain environments the social wasp Vespula pennsylvanica was a more effective pollinator than the honey bee (Thomson, 2018). Ecologists have a responsibility to ensure that the full potential of insects is realised in the health and economy of the global ecosystem (Prather & Laws, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have emphasized the need to ensure diversity and abundance of wild pollinators and the importance of protecting non-bees as a way to enhance pollination services (Blüthgen and Klein, 2011;Albrecht et al, 2012;Thomson, 2019) and crop production (Rader et al, 2013). The protection of the associated crop biodiversity is seen as an important element to ensure food security and sustainability of agricultural systems (FAO, 2018).…”
Section: Discussionmentioning
confidence: 99%